Structural health monitoring: modeling of simultaneous effects of strain, temperature, and vibration on the structure using a single apodized π-Phase shifted FBG sensor - Farinaz Kouhrangiha; Mojtaba Kahrizi; Khashayar Khorasani (Results in Optics, 2022)
There are vast fields of application for optical fiber sensors. Fiber Bragg Gratings (FBGs) are commonly used for Structural Health Monitoring (SHM) as an optical sensor to detect various physical phenomena affecting the system to assess its structure in a reliable and accurate manner. Due to the cross-sensitivity of the FBG detection, identifying the effects of each individual parameter on the FBG is a nontrivial task. This paper describes theoretical analysis of a single π-Phase Shifted Fiber Bragg Grating(π-PSFBG) behavior under axial distributions of three simultaneous parameters. Moreover, numerical simulations of an Apodized π-PSFBG are conducted to evaluate the performance of this non-uniform FBG under various strain, temperature, and vibration loads. The optimum apodization function is applied to the spectral signal to improve the properties of the sensor spectrum. Finally, the affecting parameters should be separated to determine the real cause of stress. Towards this end, the reference method is used to compensate for the strain measurements. In order to isolate the effects of stress on the structure, the performance of an apodized π-PSFBG to measure the effects of the above individual parameters on FBG is investigated and characterized with high accuracy.